Procalcitonin and cellulitis: correlation of procalcitonin blood levels with measurements of severity and outcome in patients with limb cellulitis. (17th February 2019) - Brindle, R. J.; Ijaz, A.; Davies, P.
Abstract: Background: Procalcitonin levels may be raised in bacterial infections and have been used to guide antibiotic therapy. There is little data on procalcitonin and limb cellulitis. Objectives: Within a clinical trial of antibiotic therapy, we examined the correlation between clinical observations, blood tests and local measurements of skin damage, with serum procalcitonin levels. Methods: The data is from a subset of the patients recruited into a clinical trial of antibiotic therapy for cellulitis (clindamycin for cellulitis, NCT01876628) whose procalcitonin levels were correlated with clinical and laboratory measurements. We selected the variables strongly correlated with procalcitonin and evaluated the predictive value of the baseline procalcitonin on the primary trial outcome. Results: 136 patients provided 307 procalcitonin levels which were correlated with 8 variables. The strongest correlations (correlation coefficient of >0.5) with procalcitonin were the affected skin area (0.537), C-reactive protein (0.574) and neutrophil:lymphocyte ratio (0.567). Receiver operator characteristic curves demonstrated poor sensitivity and specificity of procalcitonin in predicting primary outcome. Procalcitonin baseline levels were low but decreased as patients recovered. Conclusions: Procalcitonin levels are generally low in limb cellulitis and cannot be used to confirm the diagnosis or the need for antibiotic therapy. Procalcitonin is a poor predictor of early improvement.